Private capital flows to developing countries : (Oxford University Press for the World Bank, 1997)
The world's financial markets are rapidly integrating into a single global marketplace, and developing countries are being drawn into this process starting from different points and moving at various speeds. Those with adequate institutions and sound policies in place may proceed smoothly along the road toward financial integration and gain the many benefits that integration can bring. Most of the developing economies lack many of the necessary prerequisites for such a move; a few are so unprepared that integration may do them more harm than good. Developing countries may have little choice about whether to follow this path--advances in communications and new developments in finance have made the course inevitable--but they may still choose the ways in which they proceed, choosing the policies that benefit the economy and averting potential shocks. This World Bank report looks at the important challenges both sets of countries face in a new age of global capital. The book presents new and compelling evidence that, while low interest rates in industrial countries provided an initial impetus to the surge in private capital flows during 1989-93, these flows have entered a new phase, driven by increased financial integration. The report analyzes the causes and effects of integration, with a particular emphasis on how developing countries in the nascent stages of integration can learn from the experiences of the more rapidly integrating developing countries. The first half of the report provides the setting, analyzing the process of financial integration, the forces driving private capital to developing countries, and the potential benefits of integration. The second half looks at the domestic policy challenges that developing countries must overcome, including the macroeconomic problems of an overheating economy, reforms in the domestic financial sector, and the agenda for capital market reform.